Study of the retreating product subsidy policy based on technology thresholds of new energy vehicle consumers - Wang, Ye; Meng, Weidong; Huang, Bo; Li, Yuyu (Frontiers in Energy Research, 2022)
The new energy vehicle (NEV) product subsidy policy did not achieve a satisfactory effect on encouraging enterprise R&D as the government ignored the consumer technology thresholds——the minimum requirements of NEV consumers on a specific technology or performance of NEV. We built a game model under subsidies among the government, NEV companies, and NEV consumers considering NEV consumer characteristics such as technology thresholds. We solved the optimal retreating product subsidy policy of the government. We also analyzed the incentive effect, efficiency, and application scope of product subsidy policies and the impacts of the technology thresholds on them. We found that the government should subsidize NEV firms with medium R&D ability and encourage them to upgrade NEV technical level to the upper limit in the current stage or the highest level under financial constraints. The government should gradually reduce the unit subsidy until withdrawn with the improvement of the R&D ability of NEV firms. The technology thresholds increase the optimal unit subsidy and decrease the subsidy efficiency. Furthermore, the retreating policy is a cherry-picking subsidy method that causes companies with lower R&D ability to drop R&D.